Challenging Security Issues Using BIG Data on Mobile Application Development - Guptha1, K Gurnadha; V Vuna, Vidya Sagar; GOPAIAH, J.; Goud, K Ram Mohan; Anuradha, K (IJRDO -Journal of Computer Science Engineering, 2015)
The present paper highlights big data-specific security, privacy challenges, high volume inter-cloudcomputing, Big data, Hadoop Environment to the various rules determined by the actions taken by variousorganizations and companies benefit large scale and small scale industries. They promise new frontiers inscience. Some companies are able to use big data for high efficiency. Security and privacy are focus byvelocity, volume, and variety of big data, Cloud infrastructures, and distinct sources of data and stream ofnature of acquisition. Mobile devices have virtually become many people's fifth appendage. The result is ahuge flow of data from Smart-phones and tablets to organizations, which are struggling to manage and utilizethat information. The traditional security mechanism are tailored to secure small-scale static opposes andstream data inadequacy. Expectations highlight challenges and bring renewed focus fortifying big datainfrastructures. Cloud computing security includes rapid pace to computer security, network security,information security and data privacy. Data is protected in large and related infrastructure with policies,technologies, controls and big data tools. Mobile today can build applications which understand the users towork with the information and help in providing advice and recommendations.